Students’ Perception on Acquisition of Basic Clinical Skills (Medical Forum Monthly, 2024)
Objective: To analyze the perception of medical students towards the basic clinical skills workshops conducted during their final year in a Pakistani medical college.Study Design: Cross sectional surveyPlace and Duration of Study: This study was conducted at the Department of Medical Education, Wah Medical College, Wah Cantt, Rawalpindi during February 2012.Materials and Methods: Fifty final year students were divided into five batches for the workshop. Each batch rotated through five stations with allocated basic clinical skills. The students practiced the skills on dummies and manikins after demonstrations and instructions by the facilitators. A predesigned likert scale questionnaire with thirteen close ended questions with five options each was filled by students anonymously at the end of the workshop. Frequencies of answers were calculated.Results: Majority of students gave positive response about the conduct of the workshop and quality of facilitation. They agreed on having an improvement in their level of clinical competence post workshop. Majority suggested that the workshop should be conducted at the beginning of the final year. Although 70% thought that the skills included were relevant, however, almost a quarter remained undecided on the matter.Conclusion: The students appreciated the importance, conduct and arrangements of the workshop, and quality of facilitation. Kinesthetic learning based workshops on basic clinical skills should be a regular practice and must be conducted at the beginning of final year class of undergraduate medical education.